Pemberdayaan Masyarakat melalui Sosialisasi Pemanfaatan Oli Bekas sebagai Bahan Bakar Kompor Ramah Lingkungan di Desa Bangun Mulya Kabupaten Penajam Paser Utara - Veryyon Harahap; Noval Dzacky Nur Syachrani; Damar Feiza Samudra (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The indiscriminate disposal of used oil has the potential to cause environmental pollution and health risks, as it is classified as Hazardous and Toxic Materials (B3) waste. This community service activity aims to increase public understanding of used oil waste management through its use as environmentally friendly stove fuel. The activity was conducted in Bangun Mulya Village, Waru District, Penajam Paser Utara Regency, involving five participants consisting of vehicle repair shop owners and household members. The method used was a descriptive qualitative approach with participatory methods through initial observation, socialization of the dangers of B3 waste, demonstrations of making and using used oil-fueled stoves according to Occupational Safety and Health (K3) procedures, and activity evaluation. Evaluation was conducted through participatory observation, reflective discussions, and participant understanding questionnaires. The results of the activity showed that approximately 76% of participants experienced an increased understanding of the dangers of used oil waste, B3 waste management, and K3 procedures for stove use. The stoves were able to ignite with a stable flame after a simple filtration process, demonstrating that the use of appropriate technology can increase public awareness of safer and more productive waste management.